2019
DOI: 10.1371/journal.pone.0214422
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria from the endosphere and rhizosphere of Quercus spp. use mainly cell wall-associated enzymes to decompose organic matter

Abstract: Due to the ability of soil bacteria to solubilize minerals, fix N2 and mobilize nutrients entrapped in the organic matter, their role in nutrient turnover and plant fitness is of high relevance in forest ecosystems. Although several authors have already studied the organic matter decomposing enzymes produced by soil and plant root-interacting bacteria, most of the works did not account for the activity of cell wall-attached enzymes. Therefore, the enzyme deployment strategy of three bacterial collections (gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 68 publications
3
17
0
Order By: Relevance
“…Of 72 isolates, strain ALA1, ALA3, ALA4, and ALA5 exhibited maximum production of extracellular amylase, cellulase, and inulinase. In accordance with the previous reports ( Singh and Kumari, 2016 , Hussain et al, 2017 , Guttikonda et al, 2017 , Dida, 2018 , Manzum and Al Mamun, 2018 , Ramapriya et al, 2018 , Lasa et al, 2019 ) who demonstrated soil bacteria as ideal producers of enzymes, our findings revealed comparatively higher production of amylase, cellulase, and inulinase from Bacillus spp. and Glutamicibacter sp.…”
Section: Discussionsupporting
confidence: 93%
“…Of 72 isolates, strain ALA1, ALA3, ALA4, and ALA5 exhibited maximum production of extracellular amylase, cellulase, and inulinase. In accordance with the previous reports ( Singh and Kumari, 2016 , Hussain et al, 2017 , Guttikonda et al, 2017 , Dida, 2018 , Manzum and Al Mamun, 2018 , Ramapriya et al, 2018 , Lasa et al, 2019 ) who demonstrated soil bacteria as ideal producers of enzymes, our findings revealed comparatively higher production of amylase, cellulase, and inulinase from Bacillus spp. and Glutamicibacter sp.…”
Section: Discussionsupporting
confidence: 93%
“…This means that the planting layout of the poplars (0.5 × 2m) was effective in ensuring that their root development positively stimulated the overall microbial community in each planted plot. The positive "rhizosphere effect" has been reported by other authors [26,27] and was presumably due to the root surface releasing several organic compounds into the adjacent soil. Roots release low-molecular-weight exudates (e.g.…”
Section: Discussionsupporting
confidence: 64%
“…This means that the planting layout of the poplars (0.5 × 2 m) was effective in ensuring that their root development positively stimulated the overall microbial community in each planted plot. The positive "rhizosphere effect" has been reported by several authors (Thomas and Cébron, 2016;Lasa et al, 2019b;Schneijderberg et al, 2020) and was presumably due to the root surface releasing several organic compounds into the adjacent soil. Roots release low-molecular-weight exudates (e.g., sugars, polysaccharides, amino acids, aromatic acids, aliphatic acids, fatty acids, sterols, phenolic compounds, enzymes, proteins, plant growth regulators, and secondary metabolites) which attract soil microorganisms into the rhizosphere, where they multiply by several orders of magnitude (Badri et al, 2009).…”
Section: Discussionmentioning
confidence: 64%
“…Extraction of environmental RNA and DNA (eDNA) from each soil sample (Rhizo, Bulk and Control) was carried out using the RNA Power Soil Total RNA Isolation Kit and the DNA Elution Accessory kit (Qiagen), following the manufacturer’s recommendations. In order to evaluate the putative active bacteria in Rhizosphere and Bulk Soil, the same soil samples were used for RNA extraction; the latter was extracted as reported above and ds-cDNA synthesized in accordance with ( Lasa et al, 2019b ). Both eDNA and ds-cDNA were used as templates for MiSeq Illumina sequencing of the hypervariable V4–V5 region of the 16S rRNA gene, using the U519F and U926R primers ( Baker et al, 2003 ).…”
Section: Methodsmentioning
confidence: 99%